Educational hypermedia in nursing assistance at birth: building and validation of content and appearance - Lara Leite de Oliveira; Igor Cordeiro Mendes; Marianne Maia Dutra Balsells; Elizian Braga Rodrigues Bernardo; Régia Christina Moura Barbosa Castro; Priscila de Sousa Aquino; Ana Kelve de Castro Damasceno (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to build an educational hypermedia about nursing care at usual risk birth and to perform validation of content and appearance. Method: methodological research carried out following the following stages: content and planning of modules; media production and organization of tutorial units; organization of student space, tutor and communication between them; availability of hypermedia; assessment by experts in nursing and informatics; and implementation of proposed suggestions. Results: educational hypermedia showed to be a validated material, since it presented an optimum index of global content of 0.97 and statistical significance in the binomial test for the content and appearance. Conclusion: it is believed that the use of this material with undergraduate students in nursing will contribute to the quality of obstetric care, considering that it is an illustrated technology capable of favoring teaching-learning about normal humanized childbirth.